1992
DOI: 10.1002/ajim.4700220313
|View full text |Cite
|
Sign up to set email alerts
|

Microgranulomatous aspergillosis after shoveling wood chips: Report of a fatal outcome in a patient with chronic granulomatous disease

Abstract: Chronic granulomatous disease is characterized by recurrent infections that result from an inability of phagocytes to kill organisms effectively. We describe a patient with this disease who developed aspergillus pneumonia after shoveling moldy cedar wood chips. Despite aggressive therapy, the patient's condition deteriorated and he died. At autopsy, the lungs revealed diffuse granulomas, all of the same age, with aspergillus organisms confined to the granulomas. We propose the term "microgranulomatous aspergil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Blood cultures were positive in one mycotic pseudoaneurysm due to A. fumigatus [126], one A. nidulans endocarditis [86], fungemia due to C. lusitaniae [54] and T. pullulans [115]. Histopathologic and direct microscopic examination of a biopsy taken during open surgery was conclusive in the 7 additional proven cases [39,59,60,85,96,108,113]. Percutaneous fine needle biopsy was performed in 16 % ( n = 19), including 11 fine needle lung biopsies.…”
Section: Culture and Biopsy Of Clinical Specimensmentioning
confidence: 99%
“…Blood cultures were positive in one mycotic pseudoaneurysm due to A. fumigatus [126], one A. nidulans endocarditis [86], fungemia due to C. lusitaniae [54] and T. pullulans [115]. Histopathologic and direct microscopic examination of a biopsy taken during open surgery was conclusive in the 7 additional proven cases [39,59,60,85,96,108,113]. Percutaneous fine needle biopsy was performed in 16 % ( n = 19), including 11 fine needle lung biopsies.…”
Section: Culture and Biopsy Of Clinical Specimensmentioning
confidence: 99%
“…6 16 Conrad et al described a 32 year old patient with CGD who developed a fatal diffuse granulomatous pneumonia after shovelling wood chips. 17 Pending further studies, we recommend the consideration of chronic antifungal prophylaxis for patients with CGD if there is evidence of colonisation with Aspergillus species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, every one of these patients had suppurative granulomas as a response to the Aspergillus invasion. The histopathology of this form of IPA has been described commonly only for CGD in which Aspergillus bronchopneumonia has been noted with some frequency [8,15,16]. KELLY et al [8], in a retrospective examination of IPA in patients without major risk factors, suggested that Aspergillus bronchopneumonia with suppurating granulomas is sufficiently distinctive to suggest CGD when no other risk factor is present.…”
Section: Discussionmentioning
confidence: 99%